Weighing the necessities and concerns of deprescribing among older ambulatory patients and primary care trainees: a qualitative study - Sheron Sir Loon Goh; Pauline Siew Mei Lai; Siti Nurkamilla Ramdzan; Kit Mun Tan (BMC Primary Care, 2023)
Abstract Background Deprescribing can be a challenging and complex process, particularly for early career doctors such as primary care trainees. To date, there is limited data from patients’ and doctors’ perspectives regarding the deprescribing of medications in older persons, particularly from developing countries. This study aimed to explore the necessities and concerns of deprescribing in older persons among older ambulatory patients and primary care trainees. Methods A qualitative study was conducted among patients and primary care trainees (known henceforth as doctors). Patients aged ≥ 60 years, having ≥ 1 chronic disease and prescribed ≥ 5 medications and could communicate in either English or Malay were recruited. Doctors and patients were purposively sampled based on their stage of training as family medicine specialists and ethnicity, respectively. All interviews were audio-recorded and transcribed verbatim. A thematic approach was used to analyse data. Results Twenty-four in-depth interviews (IDIs) with patients and four focus group discussions (FGDs) with 23 doctors were conducted. Four themes emerged: understanding the concept of deprescribing, the necessity to perform deprescribing, concerns regarding deprescribing and factors influencing deprescribing. Patients were receptive to the idea of deprescribing when the term was explained to them, whilst doctors had a good understanding of deprescribing. Both patients and doctors would deprescribe when the necessity outweighed their concerns. Factors that influenced deprescribing were doctor-patient rapport, health literacy among patients, external influences from carers and social media, and system challenges. Conclusion Deprescribing was deemed necessary by both patients and doctors when there was a reason to do so. However, both doctors and patients were afraid to deprescribe as they ‘didn’t want to rock the boat’. Early-career doctors were reluctant to deprescribe as they felt compelled to continue medications that were initiated by another specialist. Doctors requested more training on how to deprescribe medications.